2013
DOI: 10.1007/s10549-013-2470-9
|View full text |Cite
|
Sign up to set email alerts
|

The HER2 status of disseminated tumor cells in the bone marrow of early breast cancer patients is independent from primary tumor and predicts higher risk of relapse

Abstract: Overexpression of the HER2-receptor in early breast cancer (EBC) patients is associated with aggressive tumor behavior. However, women suffering from HER2-positive EBC benefit from trastuzumab treatment. As the HER2 status of the primary tumor may differ from that of disseminated tumor cells (DTC) in bone marrow (BM), the aim of this study was (1) to compare the HER2 status of the primary tumor (prim-HER2-status) with that of DTC (DTC-HER2-status) and (2) to analyze the influence of the DTC-HER2-status on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 51 publications
3
27
1
2
Order By: Relevance
“…In this study, a clear discordance was found between primary tumor and DTCs. The acquisition of HER2 amplification in DTCs, while the primary tumor is negative, can be explained with a selective advantage conferred by HER2 to DTCs during dissemination [21,25,47,48,49,50], or with a higher tendency of the HER2-positive DTC clones to detach from the primary tumor and to spread [25,48,49,50,51,52]. We found that 23.6% of patients presented a HER2-negative primary tumor and HER2-positive DTCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a clear discordance was found between primary tumor and DTCs. The acquisition of HER2 amplification in DTCs, while the primary tumor is negative, can be explained with a selective advantage conferred by HER2 to DTCs during dissemination [21,25,47,48,49,50], or with a higher tendency of the HER2-positive DTC clones to detach from the primary tumor and to spread [25,48,49,50,51,52]. We found that 23.6% of patients presented a HER2-negative primary tumor and HER2-positive DTCs.…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination of tumor cells in the BM is considered responsible for the further development of the disease followed by metastasis [19,20]. Between 20 and 45% of patients with primary BC already show single tumor cells in the BM at the first diagnosis: DTCs' detection allows the identification of patients with a high risk of recurrence [17,18,21]. The percentage of patients positive for DTCs rises up to 70% in case of metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…These persistent DTCs were also shown to be of negative prognostic value [25,26]. Hartkopf et al demonstrated that persistence of DTCs after systemic treatment is a strong and independent marker of reduced disease-free and overall survival [27]. Thus, presence of isolated tumor cells in BM of breast cancer patients is regarded as a surrogate marker of minimal residual disease.…”
Section: Clinical Relevance Of Dtc Detection In Bone Marrowmentioning
confidence: 99%
“…L'amplification d'HER2 pouvant survenir lors de l'évolution de la maladie, il est primordial de pouvoir suivre la modulation phénotypique. Ainsi, des essais cliniques évaluent le bénéfice du traitement par trastuzumab sur la base du statut HER2 des CTCs (DETECT III) [14,49,50]. Cette différence phénotypique a également été décrite pour les récepteurs hormonaux.…”
Section: Utilisation Des Ctcs Pour La Personnalisation Des Traitementunclassified